2022
DOI: 10.3389/fbioe.2022.855715
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Hetero- and Phototrophic Metabolic Modules for Redox-Intensive Whole-Cell Biocatalysis

Abstract: The successful realization of a sustainable manufacturing bioprocess and the maximization of its production potential and capacity are the main concerns of a bioprocess engineer. A main step towards this endeavor is the development of an efficient biocatalyst. Isolated enzyme(s), microbial cells, or (immobilized) formulations thereof can serve as biocatalysts. Living cells feature, beside active enzymes, metabolic modules that can be exploited to support energy-dependent and multi-step enzyme-catalyzed reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 240 publications
0
4
0
Order By: Relevance
“…One obvious reason may be that reductant supply by photosynthesis is or becomes limited, either due to external factors like light limitation or restricted metabolic/photosynthetic capacity. Previous studies on Synechocystis expressing reductant‐dependent enzymes elucidated that respective reaction rates are light‐dependent (Hobisch et al ., 2021; Hoschek et al ., 2019; Tüllinghoff et al ., 2022), but also showed that light limitation could largely be relieved at high light intensities (Theodosiou et al ., 2022). In the long term, however, increasing the light intensity did not enable a recovery of decreasing C‐one biotransformation activities (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One obvious reason may be that reductant supply by photosynthesis is or becomes limited, either due to external factors like light limitation or restricted metabolic/photosynthetic capacity. Previous studies on Synechocystis expressing reductant‐dependent enzymes elucidated that respective reaction rates are light‐dependent (Hobisch et al ., 2021; Hoschek et al ., 2019; Tüllinghoff et al ., 2022), but also showed that light limitation could largely be relieved at high light intensities (Theodosiou et al ., 2022). In the long term, however, increasing the light intensity did not enable a recovery of decreasing C‐one biotransformation activities (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Since recently, phototrophic microorganisms are studied for redox biotransformations, thereby making more efficient use of photosynthesis as compared to biomass formation via the direct coupling of biocatalytic electron/energy sinks to energy source utilization, that is, the photosynthetic light reaction (Barber, 2009). Redox biotransformations are especially attractive since the separately added biotransformation substrate does not directly interfere with the host C‐metabolism (Theodosiou et al ., 2022; Toepel et al ., 2023). Thereby, these biotransformations function as (external) sinks utilizing photosynthesis‐derived energy—in the form of reduction equivalents—that may not be used by the CBB cycle due to its lower turnover capacity compared to the light reaction.…”
Section: Introductionmentioning
confidence: 99%
“…This allows conversion of externally supplied substrates, reduction of interference with host Cmetabolism, and even exploitation of surplus reduction potential not used to fuel rate-limiting C-fixation. [5] It has been shown that heterologous electron-demanding reactions indeed can tap unused potential of photosynthesis by relieving the socalled sink limitation, which is the limitation of photosynthesis by the lack of available electron sinks. [6] Among the various electron-consuming enzymes, oxygenases are of special interest for application in cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the direct harvesting of high‐energy‐electrons to drive redox reactions is especially attractive. This allows conversion of externally supplied substrates, reduction of interference with host C‐metabolism, and even exploitation of surplus reduction potential not used to fuel rate‐limiting C‐fixation [5] . It has been shown that heterologous electron‐demanding reactions indeed can tap unused potential of photosynthesis by relieving the so‐called sink limitation, which is the limitation of photosynthesis by the lack of available electron sinks [6]…”
Section: Introductionmentioning
confidence: 99%